2017
DOI: 10.1111/bph.13736
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the excitatory ‘Cys‐loop’ GABA receptor family in Caenorhabditis elegans

Abstract: BACKGROUND AND PURPOSEIonotropic GABA receptors are evolutionarily conserved proteins that mediate cellular and network inhibition in both vertebrates and invertebrates. A unique class of excitatory GABA receptors has been identified in several nematode species. Despite wellcharacterized functions in Caenorhabditis elegans, little is known about the pharmacology of the excitatory GABA receptors EXP-1 and LGC-35. Using a panel of compounds that differentially activate and modulate ionotropic GABA receptors, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The C. elegans lgc-35 cDNA was isolated and cloned into the Xenopus laevis expression vector pSGEM (a gift from M. Hollman) as previously described ( Jobson et al 2015 ; Nicholl et al 2017 ). All animal care and experimental procedures followed the guidelines from the National Institutes of Health (NIH) and the Institutional Animal Care and Use Committee (IACUC) at the University of Michigan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. elegans lgc-35 cDNA was isolated and cloned into the Xenopus laevis expression vector pSGEM (a gift from M. Hollman) as previously described ( Jobson et al 2015 ; Nicholl et al 2017 ). All animal care and experimental procedures followed the guidelines from the National Institutes of Health (NIH) and the Institutional Animal Care and Use Committee (IACUC) at the University of Michigan.…”
Section: Methodsmentioning
confidence: 99%
“…The standard bath solution for dose-response experiments was Frog Ringer’s: 115 mM NaCl, 2 mM KCl, 1.8 mM CaCl 2 , 10 mM HEPES (pH = 7.4, NaOH). Standard two-electrode voltage clamp recordings were performed as previously described ( Nicholl et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…EXP-1 and LGC-35 subunit have all the characteristic domains of a typical ionotropic GABA receptor subunit but with specific amino-acids in the pore-forming domain that confer cation selectivity ( Beg and Jorgensen, 2003 ). EXP-1 and LGC-35 share 53% sequence identity and express as cation-permeable homomeric channels in Xenopus oocytes that were more sensitive to GABA (EXP-1 EC 50 =26.4 ± 1.08 μM; LGC-35 EC 50 =17 ± 0.71 μM) in comparison to muscimol (EXP-1 EC 50 =250.0 ± 22.0 μM; LGC-35 EC 50 =348.0 ± 17.0 μM) ( Beg and Jorgensen, 2003 ; Nicholl et al, 2017 ). The pharmacological profile of EXP-1 and LGC-35 channels were more similar to GABA A -ρ family than GABA A receptors with notable pharmacological differences that distinguishes them from vertebrate and other nematode GABA channels ( Nicholl et al, 2017 ).…”
Section: Ligand-gated Ion Channelsmentioning
confidence: 99%
“…In mammals, GABA can also play the role of an excitatory neurotransmitter, and this effect results from the inversion of the chloride gradient that causes cellular depolarization (37). Excitatory GABA receptors have been described in Caenorhabditis elegans in which they play important roles in muscular contraction (38). Conversely, GABA-mediated excitatory neurotransmission has never been observed in insects (39,40), although it has been clearly demonstrated that the D. melanogaster GRD and LCCH3 subunits assemble in cationic ligandgated channels in X. laevis oocytes (19).…”
Section: Gaba-gated Ion Channels In Varroa Destructormentioning
confidence: 99%